SEMIOTIKA DALAM PERIKLANAN - Sri Hesti Heriwati (Pendhapa, 2010)
To send the message of communication by entrusting it on an object, in this case advertisement or an event in which many people show interest, should use accurate words. Using words inaccurately,  the message can not be understood well. A language as a means of communication and communication itself is self-expression. Not only can each language be used to analyze structurally but also using semiotic approach, especially to advertisements. Besides an activity of communication, advertising is an activity of marketing. Basically an advertisement is the product of mass culture and of industrial society culture indicated by mass production and consumptions. It means that the mass are only viewed as consumers. Communication activity creates personal interactions using clear signs. Communication is also the division of behavioral elements or life style with a set of rules and the use of signs. From communication point of view, the manipulation of elements of a message depends on who the target is and through what media the advertisement should be expressed.The presence of advertising as  public service is meant to counter commercial advertisements because  they are often accused of increasing consumerism. Apart from that, advertising as a public service advertisement can be viewed using semiotic approach. Key words: language, advertisement, semiotics